Some Coincidence and Common Fixed Point Theorems for Two Self Mappings under Generalized Contractive Condition in Cone-b- Metric Space - Ahmed, Tamara Sh. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we prove some coincidence and common fixed point theorems for a pair of discontinuous weakly compatible self mappings satisfying generalized contractive condition in the setting of Cone-b- metric space under assumption that the Cone which is used is nonnormal. Our results are generalizations of some recent results.